background image

3.2

Basic definitions

Definition 15

Let’s call

a funcoid

from a set

A

to a set

B

a quadruple

(

A

;

B

;

α

;

β

)

where

α

F

(

B

)

F

(

A

)

,

β

F

(

A

)

F

(

B

)

such that

∀X ∈

F

(

A

)

,

Y ∈

F

(

B

) : (

Y 6≍

α

X ⇔ X 6≍

β

Y

)

.

Further we will assume that all funcoids in consideration are small without

mentioning it explicitly.

Definition 16

Source

and

destination

of every funcoid

(

A

;

B

;

α

;

β

)

are de-

fined as

Src (

A

;

B

;

α

;

β

) =

A

and

Dst (

A

;

B

;

α

;

β

) =

B.

I will denote

FCD

(

A

;

B

)

the set of funcoids from

A

to

B

.

I will denote

FCD

the set of all funcoids (for small sets).

Definition 17

h

(

A

;

B

;

α

;

β

)

i

def

=

α

for a funcoid

(

A

;

B

;

α

;

β

)

.

Definition 18

(

A

;

B

;

α

;

β

)

1

= (

B

;

A

;

β

;

α

)

for a funcoid

(

A

;

B

;

α

;

β

)

.

Proposition 4

If

f

is a funcoid then

f

1

is also a funcoid.

Proof

It follows from symmetry in the definition of funcoid.

Obvious 4.

(

f

1

)

1

=

f

for a funcoid

f

.

Definition 19

The relation

[

f

]

P

(

F

(Src

f

)

×

F

(Dst

f

))

is defined (for every

funcoid

f

and

X ∈

F

(Src

f

)

,

Y ∈

F

(Dst

f

)

) by the formula

X

[

f

]

Y

def

=

Y 6≍

h

f

i X

.

Obvious 5.

X

[

f

]

Y ⇔ Y 6≍ h

f

i X ⇔ X 6≍

f

1

Y

for every funcoid

f

and

X ∈

F

(Src

f

),

Y ∈

F

(Dst

f

).

Obvious 6.

f

1

=[

f

]

1

for a funcoid

f

.

Theorem 4

Let

A

,

B

are small sets.

1. For given value of

h

f

i

exists no more than one funcoid

f

FCD

(

A

;

B

)

.

2. For given value of

[

f

]

exists no more than one funcoid

f

FCD

(

A

;

B

)

.

Proof

Let

f, g

FCD

(

A

;

B

).

Obviously

h

f

i

=

h

g

i ⇒

[

f

]=[

g

] and

f

1

=

g

1

[

f

]=[

g

]. So it’s enough

to prove that [

f

]=[

g

]

⇒ h

f

i

=

h

g

i

.

Provided that [

f

]=[

g

] we have

Y 6≍ h

f

i X ⇔ X

[

f

]

Y ⇔ X

[

g

]

Y ⇔ Y 6≍

h

g

i X

and consequently

h

f

i X

=

h

g

i X

for every

X ∈

F

(

A

) and

Y ∈

F

(

B

)

because a set of filter objects is separable [15], thus

h

f

i

=

h

g

i

.

10